2007
DOI: 10.1016/j.socscimed.2006.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the urban environment: A scale measure of urbanicity outperforms the urban–rural dichotomy

Abstract: The rapid urbanization of the developing world has important consequences for human health. Although several authorities have called for better research on the relationships between urbanicity and health, most researchers still use a poor measurement of urbanicity, the urban-rural dichotomy. Our goal was to construct a scale of urbanicity using community level data from the Cebu Longitudinal Health and Nutrition Survey. We used established scale development methods to validate the new measure and tested its pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
215
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(222 citation statements)
references
References 23 publications
(39 reference statements)
7
215
0
Order By: Relevance
“…It was conducted in three steps: (i) constructing a measure of urbanicity using a validated scale 8 based on data from the Census of India 2001; (ii) calculating the prevalence of NCD risk factors in seven study areas in the state of Tamil Nadu, India, by using data from an NCD risk factor surveillance survey conducted locally in 2003-2004 as part of a larger study 9 ; and (iii) testing for an association between urbanicity and the prevalence of NCD risk factors in the study areas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was conducted in three steps: (i) constructing a measure of urbanicity using a validated scale 8 based on data from the Census of India 2001; (ii) calculating the prevalence of NCD risk factors in seven study areas in the state of Tamil Nadu, India, by using data from an NCD risk factor surveillance survey conducted locally in 2003-2004 as part of a larger study 9 ; and (iii) testing for an association between urbanicity and the prevalence of NCD risk factors in the study areas.…”
Section: Methodsmentioning
confidence: 99%
“…An existing composite continuous measure of urbanicity previously used and validated for the Philippines by Dahly and Adair 8,10 was identified through an earlier systematic review. 11 It comprised seven elements: population size, population density, access to markets, communications, transport, education and health services.…”
Section: Measuring Urbanicitymentioning
confidence: 99%
“…When categorized, with the most similar regions in one group according to density, it is easier to understand the impact of urbanization, rather than comparing the effect of the individual population in each region [1]. One of the crucial factors in defining the urbanization level is the population size and the density [25]. Therefore, considering the population distribution shown in Table 1, the five watersheds in Kelani River were classified into three categories as urbanized level one (UL1), which has a higher population, urbanized level two (UL2) which has intermediate population, and urbanized level three (UL3) which has lower population.…”
Section: Analysis Of Correlationmentioning
confidence: 99%
“…This review demonstrated the paucity of multi component measures of urbanization as a risk factor for NCDs and established the need for a measure of urbanization sensitive enough to track changes in urbanicity and subsequent emergence of chronic diseases or their risk factors. 24 Mendez and Popkin 25 created one of the few multicomponent measures which included ten components: population size, population density, access to markets, transportation, communications/media, economic factors, environment/sanitation, health, education, and housing quality. Dahly and Adair 24 refined this tool into a multivariable scale and Allender et al 26 tested the feasibility of using this scale in Southern India.…”
Section: A Problem Of Measurementmentioning
confidence: 99%